Understanding and characterising collective tenure and tenure security in pastoral systems: Consolidation of case studies in Burkina Faso, Sudan and Kenya - Nassef, Magda; Otieno, Ken; Sulieman, Hussein; Sawadogo, Issa; Locke, Anna; Langdown, Ian; Flintan, Fiona E. (SPARC, 2024)
Land tenure insecurity has been highlighted as a main factor in farmer–herder conflict (Flintan, 2012; Davies et al., 2016; Nassef et al., 2023). While tenure and tenure security for settled land users has been well documented, pastoral collective tenure and degrees of tenure security in pastoral systems are not as well understood. To explore this issue, we examined collective tenure systems in Burkina Faso, Sudan and Kenya. Two layers of tenure and tenure security were considered: that of the group and that of individuals within the group, recognising that groups are not homogenous. None of the pastoral communities in this study hold any formal documentation for their land but do consider themselves rightful landholders.